(untitled) - Greenfield, Harry I. (New York, 1966)
This book introduction the scaale of producer services, the supply of producer services, the labor force in the producer services segment...
Keywords: Service industries,Labor supply,Các ngành dịch vụ,Nguồn cung cấp lao động; United States,Hoa Kỳ,Hoa Kỳ